PENERAPAN MODEL PEMBELAJARAN REFLEKTIF NILAI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS 2C SDN DEMANGAN 1 BANGKALAN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research aims to improve students’ learning outcomes in Pancasila Education, particularly on the theme of social responsibility at home and in the surrounding environment, through the implementation of the Value-Reflective Learning Model (VRLM). The study was conducted in class 2C at SDN Demangan 1 Bangkalan over two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through tests, observations, interviews, and documentation, and were analyzed using quantitative and qualitative approaches. The findings show that VRLM effectively facilitated students’ reflection on personal experiences, strengthened their moral awareness, and helped them connect Pancasila values with daily life situations. Students’ learning outcomes increased significantly, with the average score improving from 63.62 in the pre-cycle to 82.24 in Cycle I, and 95.52 in Cycle II. The percentage of students achieving mastery also rose from 24% in the pre-cycle to 93% in Cycle I, and reached 100% in Cycle II. These results indicate that VRLM not only enhances students’ cognitive understanding but also supports the internalization of social responsibility values, making learning more meaningful and learner-centered. Overall, the implementation of VRLM proved effective in improving learning quality and strengthening character education in Pancasila learning for elementary school students.